An Analysis of the Transformation of Mega-Pharma’s Business Model toward the Emerging Market - Yaeko Mitsumori (Emerging Science Journal, 2020)
The Trade-Related Aspects of Intellectual Property Rights（TRIPS) requires all member countries of the World Trade Organization (WTO) to introduce a TRIPS-compatible patent law into their countries. Due to the enforcement of TRIPS in 1995, India in 2005 revised its patent law and enacted the Patents (Amendment) Act, 2005. The 2005 ACT included product patent in pharmaceutical field. Due to the new patent law with product patent protection, large foreign capital pharmaceutical companies one after another re-entered the Indian market and started engaging in both R&D and production targeting the Indian market. However recent data shows the number of patent applications has been declining over the past several years and the number of patented drugs launched in India did not increase so rapidly. This study analyzes transitions of business models of foreign pharmaceutical companies in India based on the patent application data, and the trend of patented drugs in the market. A data analysis and a series of interviews with stakeholders were conducted. As a result of both a quantitative and a qualitative analysis, it was found that foreign pharmaceutical companies changed their strategies in the Indian pharmaceutical market. Since India was required to introduce product patents in the pharmaceutical area, there have been many arguments that once India introduces a product patent, the Indian pharmaceutical industry may decline due to the rapid introduction of foreign pharmaceutical products in the country; many academic papers were published in this context during that time. However, since 2005, when product patents were actually introduced in India, few academic papers were published. This study is unique as it discusses the effects of the introduction of product patents on the Indian pharmaceutical market.